1992
DOI: 10.1093/her/7.3.437
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of smoking behavior in Japanese young adults

Abstract: Eighty-eight second grade students of a senior high school in Saitama prefecture in Japan participated in a prospective study to predict cigarette smoking behavior 3.5 years later. Predictor variables include sex, knowledge, beliefs and attitudes toward smoking, previous smoking behavior, and smoking behavior of their families. Stepwise discriminant analyses revealed that 90% of the smokers and 65% of the non-smokers were correctly classified. In this model, previous smoking behavior proved to be the best p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Based on the results, teenagers are likely to believe that smoking looks more stylish, looks more mature, and they feel very welcome by their friends. This result is in accordance with Kawabata et. al.…”
Section: Conclusion and Recommendations Conclusionsupporting
confidence: 93%
See 2 more Smart Citations
“…Based on the results, teenagers are likely to believe that smoking looks more stylish, looks more mature, and they feel very welcome by their friends. This result is in accordance with Kawabata et. al.…”
Section: Conclusion and Recommendations Conclusionsupporting
confidence: 93%
“…Based on the results, teenagers are likely to believe that smoking looks more stylish, looks more mature, and they feel very welcome by their friends. This result supported by Kawabata, Orlandi, Takahashi (1992) that state smoking behavior proved to be the best predictor of smoking behavior based on the study in Japan among second grade students of a senior high school. Hypothesis 3 is supported.…”
Section: Research Findings and Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Smoking among peers was the best predictor of smoking for white adolescents (accounting for 23.5% of the variance) but accounted for only 15% of the variance for young Hispanics, 9.6% of the variance for young Asians, and none of the variance for young blacks. A study in Japan among second grade students of a senior high school revealed that smoking behaviour proved to be the best predictor of smoking behaviour 3.5 years later 12. Attitudes towards men’s smoking, sex, and smoking in subjects’ families were also related.…”
mentioning
confidence: 99%
“…In Japan, a few study on adolescent smoking have examined multiple factors simultaneously by using multivariate analyses and adjusted for confounding factors 11,12) . Moreover, no studies have attempted to use a risk factor approach and to show a dose-response relationship between the number of risk factors and smoking behavior among Japanese adolescents to our knowledge to date.…”
Section: Introductionmentioning
confidence: 99%